Average Error: 0.0 → 0.0
Time: 2.8s
Precision: 64
\[x + e^{-x}\]
\[x + e^{-x}\]
x + e^{-x}
x + e^{-x}
double f(double x) {
        double r24079594 = x;
        double r24079595 = -r24079594;
        double r24079596 = exp(r24079595);
        double r24079597 = r24079594 + r24079596;
        return r24079597;
}

double f(double x) {
        double r24079598 = x;
        double r24079599 = -r24079598;
        double r24079600 = exp(r24079599);
        double r24079601 = r24079598 + r24079600;
        return r24079601;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[x + e^{-x}\]
  2. Final simplification0.0

    \[\leadsto x + e^{-x}\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "x+exp(-x)"
  (+ x (exp (- x))))